STUDI LITERATUR: POPULARITAS DAN TINGKAT KEBERHASILAN ACTIVITY-BASED COSTING DI BERBAGAI NEGARA - Siahaan, Johan; Br. Tobing, Gresi Lusina; Dolok Saribu, Ardin; Hutahaean, Marlia Olivia; Sembiring, Anisa Putri; Silaban, Ester; Miranda, Elsa; Simanjuntak, Evelyn (JURNAL AKUNTANSI BARELANG, 2024)
This study aims to determine the popularity of Activity-Based Costing (ABC) methods and the success rates of countries adopting the ABC system. The research method used is a literature review. The main journal was used as a basis for comparison. The abstract is "Activity Based-Costing Around The World: Adoption, Implementation, Outcomes, and Criticism," supported by 20 other journals, both international and national. The most commonly used method in the supporting journals is the descriptive qualitative method. The study results show that the popularity of the ABC method is still dominated by Western (European) countries, which are generally developed countries. Meanwhile, in Asia and Africa, only a few companies implement the ABC method due to internal and external obstacles within the organization. On the other hand, some ABC-adopting countries, have different success rates in its implementation. This variation is generally caused by the availability of organizational resources, different levels of support from top management, and most commonly, insufficient understanding and knowledge about ABC.